329 Heart failure predictive value of the electric risk score in patients suffering from thalassemia major. (8th December 2021) - Tomarelli, Elisa; Moscucci, Federica; Losardo, Anna Annunziata; Pugliese, Pellegrina; Schina, Mauro; Sciomer, Susanna
Abstract: Aims: Complications associated with iron accumulation were highly recurrent in thalassemia patients, who underwent frequent blood transfusions, in particular hemosiderotic cardiomyopathy which could lead to heart failure and arrhythmias. Nowadays, the better iron chelation therapy has improved cardiovascular morbidity in these patients; nevertheless, mild impairment should be seek for and eventually treated. The objective of our study was to evaluate the possibility of using early electrocardiographic markers of myocardial damage and predictors of mortality, such as the Electric Risk Score (ERS). Methods and results: 73 patients with thalassemia major were enrolled in this study, which were divided into two groups, with 45 years old as cut off. Anamnestic, clinical, electrocardiographic, and echocardiographic data were collected. From ECG, ERS was obtained. over 45 yrs-old group of pts, in addition to a predictable increase in the prevalence of traditional cardiovascular risk factors and drug intake, an alteration of the QRS-T angle (14[30] vs. −4[28], p value: <0.0001) and an increased prevalence of left ventricular hypertrophy (2.88 ± 0.86 vs. 2.40 ± 0.57 p value: <0.05) were found. In patients taking drugs with possible interactions with the ventricular repolarization phase, there is a slight increase in the QT interval, left ventricular hypertrophy and a reduction in Tpeak-Tend (Table 1). Electrocardiographic values in groups of patients with different age groups who are taking therapies that can affect QT. The echocardiogram revealed an increase in the end-diastolic diameter of the right ventricle (26 ± 3 vs. 28 ± 3 mm, P -value: 0.05) in the group of patients over the age of 45, a decrease in the acceleration time of the pulmonary systolic flow (138 ± 25 vs. 125 ± 13 ms, P -value: 0.04) and TAPSE (25 ± 3 vs. 22 ± 4 mm, P -value: 0.002). Conclusions: From the data in our study it emerged that an appropriate iron-chelation therapy is able to effectively counteract the hemosiderotic cardiomyopathy of thalassemic patients so as to detect electro- and echocardiographic anomalies only in patients of more advanced age, a result that we think both the consequence, not so much of iron overload, but of an increase in the prevalence of age- and gender-related cardiovascular risk factors. The initial changes in cardiac electromechanics, which can be assessed with the aforementioned methods, we believe, can become a very early sign of specific myocardial damage.